TRACKING LANGUAGE STUDIES, 1913–2025: WHERE HAVE WE BEEN AND WHERE ARE WE HEADED? - John Rey Pelila; Gwyneth Andogan Sildon (LP2M UIN Abdul Muthalib Sangadji Ambon, 2025)
Despite the increasing body of research on language and identity, heritage language, education, and multilingual practices, a comprehensive bibliometric overview of how these areas have evolved over time remains lacking. This gap limits our understanding of major trends, influential works, and emerging directions in the field. To address this, the study aims to conduct a bibliometric analysis of language-related research by mapping publication patterns, keyword evolution, and thematic clusters to identify scholarly developments and underexplored areas. A total of 3,638 articles published between 1913 and 2025 were retrieved from the Scopus database using refined search terms such as “first language,” “mother tongue,” “heritage language,” and “foreign language,” and filtered to include publications in the Social Sciences, Arts and Humanities, and Psychology. MS Excel and VOSviewer were employed to analyze co-authorship networks, keyword co-occurrence, and thematic structures. Findings reveal a steady increase in publication output from 2000 to 2024, with a noticeable surge during the COVID-19 pandemic. The United States and United Kingdom remain dominant in research productivity, though rising contributions from Asia and the Global South reflect a more inclusive scholarly landscape. Influential scholars such as Bialystok and Ellis continue to shape discussions on bilingualism and cognition. Major research clusters include bilingualism and identity, heritage language maintenance, language and migration, and cognitive development. The study concludes that language research is interdisciplinary, collaborative, and increasingly global in scope. It recommends greater attention to indigenous language revitalization and digital multilingualism and urges educators and policymakers to apply these insights to foster inclusive, culturally responsive language education and planning.